Reprint of "Enhancing green supply chain initiatives via empty container reuse". (February 2015) - Li, Ling; Wang, Bin; Cook, David P.
Highlights: Considered empty container repositioning with green supply chain efforts. Measured the value of reusing empty containers. Considered the weight and volume when loading a mix of laden and empty containers. Abstract: In this paper, the maritime industry's commitment to green supply chain has been analyzed. The objective of this study is to show that the reuse of empty containers not only adds value to a firm, but leads to waste reduction in the supply chain. The novelties of this article include (i) empty and laden containers are treated in accordance with a shipping company's green effort; (ii) both the volume and weight of containers are introduced to indicate a potential constraint on green effort; (iii) empty container storage costs are included as a value-added component which stem from green effort.